2004
DOI: 10.1111/j.0303-6987.2005.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Osseous metaplasia in the setting of nephrogenic fibrosing dermopathy

Abstract: We report the exceptional finding of bone metaplasia in the setting of a case of NFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 13 publications
3
36
1
Order By: Relevance
“…The fibrotic infiltration of NSF has been described to involve a variety of tissues including subcutaneous, all muscle types, pleura and pericardium, the tunica albuginea, renal tubules, great vessels of the heart extending into the ventricles and septum, as well as facial, pulmonary and cardiac fibrosis (10). Rarely, NSF may progress to dermal calcification (2,9) and even to the extreme of osseous spicules perforating the epidermis (11). A careful histopathological evaluation and the clinically distinct characteristic distribution prevents this variant of NSF to be mistaken for calciphylaxis of renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrotic infiltration of NSF has been described to involve a variety of tissues including subcutaneous, all muscle types, pleura and pericardium, the tunica albuginea, renal tubules, great vessels of the heart extending into the ventricles and septum, as well as facial, pulmonary and cardiac fibrosis (10). Rarely, NSF may progress to dermal calcification (2,9) and even to the extreme of osseous spicules perforating the epidermis (11). A careful histopathological evaluation and the clinically distinct characteristic distribution prevents this variant of NSF to be mistaken for calciphylaxis of renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Osseous metaplasia, osteoclastlike giant cells, and calciphylaxis can be seen in some NSF biopsies. [11][12][13] On a technetium 99 -diphosphosphonate scan, areas of increased uptake can be observed in muscles. 14,15 On magnetic resonance imaging, axial T1-and fat-suppressed T2-weighted images show symmetric skin thickening and soft tissue edema.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical markers such as CD34, procollagen I, CD68, and factor XIIIa have also been described as characteristic of this disorder [11,12]. Others have found that in addition to the classic histological features, dermal ossification can occur [13].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, autoimmune phenomena have been proposed to play a possible role in the pathogenesis [13], as has the presence of "circulating cytokines" [7,15] and an aberrant recruitment, activation, or proliferation of "circulating fibrocytes" [16,17]. There is no evidence of a common etiology to the skin disorder and the associated renal abnormalities.…”
Section: Discussionmentioning
confidence: 99%